Inoculum Standardization for Antifungal Susceptibility Testing of Filamentous Fungi Pathogenic for Humans - Petrikkou, Eva (American Society for Microbiology, 2001)
Two methods of inoculum preparation for filamentous fungi were compared: counting with a hematocytometer and spectrophotometric adjustment. One hundred eighty-two filamentous fungi pathogenic for humans were used. Colony counts were done for all inoculum preparations. The agreement between the hematocytometer counts and the colony counts (CFU per milliliter) was 97.2%. The reproducibility between the hematocytometer counts and the colony counts by means of an intraclass correlation coefficient was 0.70. Pearson's correlation index for hematocytometer counts versus colony counts was 0.56, whereas that for optical density versus colony counts was 0.008. Both methods can be used for inoculum size adjustment. However, the use of the spectrophotometric method requires that each species be standardized separately.